2014
DOI: 10.1039/c3cp53858c
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of CO2 solubility for hydrate formation from carbon dioxide containing water and other impurities

Abstract: Deciding on the upper bound of water content permissible in a stream of dense carbon dioxide under pipeline transport conditions without facing the risks of hydrate formation is a complex issue. In this work, we outline and analyze ten primary routes of hydrate formation inside a rusty pipeline, with hydrogen sulfide, methane, argon, and nitrogen as additional impurities. A comprehensive treatment of equilibrium absolute thermodynamics as applied to multiple hydrate phase transitions is provided. We also discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
(63 reference statements)
0
26
0
Order By: Relevance
“…1 At this stage, no attempts have been made to tune the model empirically to fit experimental data available in the open literature. The free energies of CO 2 inclusion can be found in Kvamme et al 18,19 Hydrogen sulfide, a well-known and extremely vigorous hydrate-former was considered to be one of the impurities likely to significantly impact the process of hydrate formation during pipeline transport. Since the molecular interaction model for CO 2 in this work is different from that of Kvamme and Tanaka, 1 new free energy of inclusion function parameters for this model, as well as for the H 2 S model, have been estimated and listed in Table 1 below (complementary to Table 5 of Kvamme and Tanaka 1 ).…”
Section: Thermodynamics Of Hydrate Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…1 At this stage, no attempts have been made to tune the model empirically to fit experimental data available in the open literature. The free energies of CO 2 inclusion can be found in Kvamme et al 18,19 Hydrogen sulfide, a well-known and extremely vigorous hydrate-former was considered to be one of the impurities likely to significantly impact the process of hydrate formation during pipeline transport. Since the molecular interaction model for CO 2 in this work is different from that of Kvamme and Tanaka, 1 new free energy of inclusion function parameters for this model, as well as for the H 2 S model, have been estimated and listed in Table 1 below (complementary to Table 5 of Kvamme and Tanaka 1 ).…”
Section: Thermodynamics Of Hydrate Formationmentioning
confidence: 99%
“…7,8,10,[18][19][20][21] Most hydrate risk evaluation tools are based on liquid water formation through eqn (4) and subsequent hydrate formation together with hydrate formers from the carbon dioxide phase. Further progress towards hydrate can continue both at the interface between water and carbon dioxide and from hydrate formers dissolved in water.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the impurities may result in the formation of gaseous CO 2 or two-phase CO 2 flow inside the pipelines. The water content in the CO 2 stream results in the risk of hydrate, which will pose a complex problem involving phase transient and pipeline blockage [13,[15][16]. Therefore, before the transport, the CO 2 stream has to be conditioned to remove impurities such as water vapour, H 2 S, N 2 , methane, O 2 , hydrocarbons and free water [17][18].…”
Section: Previous Studiesmentioning
confidence: 99%
“…Furthermore, concerns have been raised about the kinetic effects on clathrate hydrates formation and composition. Kvamme et al [22] reported that mixed gas hydrates might not be theoretically reached at equilibrium by reassessing the Gibbs phase rule and the laws of thermodynamics.…”
Section: Introductionmentioning
confidence: 99%